Indirect control of single-phase active power filters using harmonic control arrays - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
The ever increase of nonlinear loads in electric distribution networks causes many problems due to the high level of harmonic currents. This paper proposes a new technique for controlling a single phase shunt active power filter based on a selective compensation using the newly developed technique of harmonic control arrays. Simulation results confirm the appropriate selective harmonic compensation performance under different operating conditions. © 2017 IEEE.
Keywords: Electric distribution network; Harmonic control arrays; Selective compensation; Single-phase active power filter